The finite-difference time-domain for electromagnetics : with MATLAB simulations - Elsherbeni, Atef Z.; Demir, Veysel, 1974- (ACES series on computational electromagnetics and engineering., 2016)
This book introduces the powerful Finite-Difference Time-Domain method to students and interested researchers and readers. An effective introduction is accomplished using a step-by-step process that builds competence and confidence in developing complete working codes for the design and analysis of various antennas and microwave devices.